A Cybernetic Metric Approach to Course Preparation - Russell Jay Hendel (Journal of Systemics, Cybernetics and Informatics)

(untitled)
This paper reviews and unifies 15 papers and book chapters written by the author over the past decade. The paper shows that an underlying commonality of all the author's approaches to a wide variety of pedagogical problems relies on three pillars: (a) a cybernetic approach that is independent of discipline and does not rely on specific content areas, (b) direct referral to established processes of the mind, and (c) a metric approach whereby a new pedagogic tool is formulated in terms of measurement enabling newcomers to instantly apply the new method. These three pillars are useful in improving all aspects of course pedagogy: delivery, retention, performance, and satisfaction. The use of a metric approach is often superior (easier to implement) than traditional approaches; the appeal to direct processes of the mind supplements reliance on experiments and surveys which focus on methods rather than on their underlying psychological basis. The three pillars apply to such diverse areas as pedagogic challenge, syllabus construction, computer assisted instruction (CAI), dealing with hard course components, formulating challenging practice exercises, enriching syllabus modules, and defining levels of problem difficulty. The mental processes on which the theory is based are executive function, atomic habit formation, Stroop interference, controllability (attribution) theory, and self-efficacy.